Application of the MUSIC method for estimation of the signal fundamental frequency - Šimonytė, Virginija; Pyž, Gražina; Slivinskas, Vytautas (Lietuvos matematikos rinkinys, 2009)
The goal of the paper is to use the MUSIC method to estimate the fundamental frequency of signals, and compare the results with the ones obtained by the DFT method. Real speech signals are considered in the paper. Lithuanian vowel sound fundamental frequency is estimated by the MUSIC and DFT methods.